Downstream Analysis of Strategic Investment in Natural Gas Commodities in Increasing the Value of Indonesian Natural Gas Products - Bhagya, Tombak Gapura; Wibowo, Jati Arie; Latipah, Siti; Prakarsa, Graha (Universitas Insan Cendekia Mandiri, 2024)
Indonesia as one of the natural gas producing countries needs to carry out product downstreaming. This is done to increase the added value of natural gas products. Natural gas exports must be reduced and converted into exports in the form of derivative products. Methanol, ammonia, urea, ammonium nitrate and soda ash are derivative products from natural gas that need to be developed. These product derivatives are used as a mixture of raw materials in various industrial sectors that are closely related to daily needs, so that the market and prices will not decrease.